The Role of Target Culture in English Language Education: EFL Teachers’ Perspectives - Mohamed, Anes; Farahani, Ali (ELT Worldwide: Journal of English Language Teaching, 2023)
This research inquired into the ways in which EFL teachers think of the role of target culture in English language education. Of special interest in this research was the issue of whether teaching the target culture is seen as important when it comes to English language learning and teaching in EFL contexts or not. Equally important was the question of whose target culture is taught. Data was collected through semi-structured interviews with ten EFL teachers at different language institutes: five were from Khartoum, Sudan and five from Tehran, Iran. The interview questions, which were formulated after extensive reading of germane literature, explored themes related to culture and its role in English language education. The main and most important finding of the research indicates that EFL teachers think that it is necessary to teach elements of the target culture that are not at odds with their local cultures. Another related finding is that the target culture is conceptualized in monolithic terms and is equated with American and British cultures.